The effect of dimethyl sulfoxide on Corynebacterium pseudotuberculosis biofilm: an in silico prediction and experimental validation - Yaacob, Mohamad Fakhri; Abdullah, Faez Firdaus Jesse; Mohamad Jamil, Norashirene; Mohamed Yunus, Norfatimah; Aazmi, Shafiq; Raja Yahya, Mohd Fakharul Zaman (Institute of Physics Publishing, 2021)
Corynebacterium pseudotuberculosis is a Gram-positive pathogen that commonly causes caseous lymphadenitis which occurs in sheep, goats, cattle, buffalo and horses. This disease has long been shown to be a major cause of economic loss on sheep industries. Dimethyl sulfoxide (DMSO) is known to be effective against a wide spectrum of pathogens however, its efficacy against C. pseudotuberculosis biofilm remains uncertain. The objective of this study was to predict the antibiofilm potential of DMSO against C. pseudotuberculosis using in silico protein interaction network analysis and experimentally determine the antibiofilm activity using standard microplate assay system. As compared to the protein interaction network of S. typhimurium biofilm that had previously been shown to be inhibited by DMSO, the protein interaction network of C. pseudotuberculosis showed similar nodes, hub proteins and functional linkages between glycolytic enzymes. Further experimental validation revealed that the treatment with DMSO significantly (p<0.05) inhibited C. pseudotuberculosis biofilm at all tested concentrations (1.56% - 50%). The findings from the present study suggest the potential application of DMSO in controlling caseous lymphadenitis in ruminants.